Patient Safety in Non-Operating Room Anesthesia (Nora) - Pratomo, Bhirowo Yudo; Sudadi; Hermawan, Hendra (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Practice in the field of non-operating room anesthesia (NORA) is associated with the risks of injury or death. The number of NORA cases recently has increased with more than half of claims related to death, due to lack of anesthetic care standard. The need for implementation standard of NORA such as equipments, staffs and facilities must meet the criteria of safety. So it is an important concern in preventing those complications. The three paradigm steps towards a systematic NORA approach encompass patient, procedures and the environment. The first step to improve patient safety in the case of NORA includes measuring preparation with adequate facilities, introductions of the location, equipments and available personnels. The training skill and communication between the anesthetist team and other support personnel are required. In addition, procedural preparation must be prepared for possible emergencies and adverse outcomes.